Exocyst complex component 1 (Exoc1) loss in dormant oocyte disrupts c-KIT and growth differentiation factor (GDF9) subcellular localization and causes female infertility in mice - Chi Lieu Kim Nguyen; Yumeno Kuba; Hoai Thu Le; Hossam Hassan Shawki; Natsuki Mikami; Madoka Aoki; Nanako Yasuhara; Hayate Suzuki; Saori Mizuno-Iijima; Shinya Ayabe; Yuki Osawa; Tomoyuki Fujiyama; et al. (Cell Death Discovery)
Abstract A limited number of female germ cells support reproduction in many mammals. The follicle, composed of oocytes and supporting granulosa cells, forms the basis of oogenesis. Crosstalk between oocytes and granulosa cells is essential for the formation, dormancy, re-awakening, and maturation of oocytes. The oocyte expresses c-KIT and growth differentiation factor-9 (GDF-9), which are major factors in this crosstalk. The downstream signalling pathways of c-KIT and GDF-9 have been well-documented; however, their intra-oocyte trafficking pathway remains unclear. Our study reveals that the exocyst complex, a heterotetrameric protein complex important for tethering in vesicular transport, is important for proper intra-oocyte trafficking of c-KIT and GDF9 in mice. We found that depletion of oocyte-specific EXOC1, a component of the exocyst complex, impaired oocyte re-awakening and cyst breakdown, and inhibited granulosa cell proliferation during follicle growth. The c-KIT receptor is localised on the oocyte plasma membrane. The oocyte-specific Kit conditional knockout mice were reported to exhibit impaired oocyte re-awakening and reduced oocyte cyst breakdown. GDF9 is a protein secreted extracellularly in the oocyte. Previous studies have shown that Gdf9 knockout mice impaired proliferation and granulosa cell multilayering in growing follicles. We found that both c-KIT and GDF9 abnormally stuck in the EXOC1-depleted oocyte cytoplasm. These abnormal phenotypes were also observed in oocytes depleted of exocyst complex members EXOC3 and EXOC7. These results clearly show that the exocyst complex is essential for proper intra-oocyte trafficking of c-KIT and GDF9. Inhibition of this complex causes complete loss of female fertility in mice. Our findings build a platform for research related to trafficking mechanisms of vital crosstalk factors for oogenesis.